2007
DOI: 10.1039/b705478e
|View full text |Cite
|
Sign up to set email alerts
|

Functional isocyanide metal complexes as building blocks for supramolecular materials: hydrogen-bonded liquid crystals

Abstract: Gold, palladium and platinum complexes with an unusual isocyanide ligand containing a carboxylic acid function, [AuCl(CNC(6)H(4)COOH)], cis-[MI(2)(CNC(6)H(4)COOH)(2)] and trans-[MI(2)(CNC(6)H(4)COOH)(2)] (M = Pd, Pt) have been isolated. The carboxylic acid group of the coordinated isocyanide acts as a hydrogen donor for hydrogen-bonding and three series of stable hydrogen-bonded liquid crystalline metal complexes have been prepared with decyloxystilbazole. Although all the metal acid derivatives used are not m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 50 publications
4
23
0
Order By: Relevance
“…We have recently reported metallomesogens based on hydrogen‐bonded supramolecular complexes formed from metalloacids derived from the combination of 4‐isocyanobenzoic acid metal complexes (4‐isocyanobenzoic metalloacids, [M]‐CNC 6 H 4 CO 2 H), and dodecylstilbazole as proton acceptor 20. 21 The thermal stability of these dodecylstilbazole aggregates is low and they disaggregate at high temperatures owing to the lability of the hydrogen bond.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently reported metallomesogens based on hydrogen‐bonded supramolecular complexes formed from metalloacids derived from the combination of 4‐isocyanobenzoic acid metal complexes (4‐isocyanobenzoic metalloacids, [M]‐CNC 6 H 4 CO 2 H), and dodecylstilbazole as proton acceptor 20. 21 The thermal stability of these dodecylstilbazole aggregates is low and they disaggregate at high temperatures owing to the lability of the hydrogen bond.…”
Section: Introductionmentioning
confidence: 99%
“…The X-ray patterns of S8 complex, recorded at 60 ºC, exhibit two sharp and intense and two weaker low-angle diffraction peaks, of decreasing intensity as a function of increasing diffracting angles, with reciprocal d spacings in the 1:√3:√7:√9 ratio. These features are unambiguously assigned to the (10), (11), (21) and (30) reflections of a hexagonal columnar phase with a lattice parameter, a = 50.45Å (Figure 3). 47 The broad low-and wideangle signals (h mol , h ch ) were associated to some weakly correlated intermolecular distances i.e.…”
Section: X-ray Diffraction Experimentsmentioning
confidence: 98%
“…These are: a few hydrogen-bonded ferrocene complexes; 23,24,25 phenanthroline copper derivatives; 26 pyrazole rhodium complexes; 27 salicyladimine derivatives of palladium, copper and vanadium; 28 dicyanometallate-based networks combined with dicationic tectons; 29 and some 4-isocyanobenzoic acid metal complexes reported by our group. 30,31,32 In our initial studies, we found that 4-isocyanobenzoic acid metal complexes (metallo- . 32 An obvious strategy to achieve more thermally stable metallomesogens of this type is to reduce the transition temperatures of the system, which can be achieved by connecting a larger number of terminal alkoxy substituents into the molecule, as in polycatenar liquid crystals.…”
Section: Introductionmentioning
confidence: 99%
“…The ligand 4-isocyanobenzoic acid was selected because it possesses an isocyanide coordinating functional group, and can leave a free carboxylic to form supramolecular by means of H-bonds with the nitrogen of the stilbazol molecule. Firstly, 4-isocyanobenzoic acid gold complexes (metallo-organic acids) were prepared, namely [AuX(CNC 6 H 4 COOH)] (X = Cl, fluoroaryl), which can act as proton donors to decyloxystilbazole, giving rise to supramolecular metal complexes displaying liquid crystalline behavior ( Figure 26) [44,45] The use of trisalkoxystilbazoles is going to reduce the transition temperatures in order to facilitate more thermally stable metallomesogens. In that way, supramolecular metal complexes formed through hydrogen bonding between tris(3,4,5-decyloxy)stilbazole and several gold-organic acids of the type [AuR(CNC 6 H 4 COOH)] have been synthesized (Figure 27) [46].…”
Section: Pyrazolate Ligandsmentioning
confidence: 99%